Missed opportunities for the detection of abdominal aortic aneurysms : a retrospective study of eighteen patients presenting with a ruptured or acute symptomatic abdominal aortic aneurysm - Maroney, Roy Thomas (Department of Public Health and Family Medicine, 2017)
A ruptured abdominal aortic aneurysm (AAA) has a mortality of 80 percent. The majority of these cases present as medical emergencies, with 50 percent dying before they reach hospital. Twenty percent are not operated on because of an incorrect diagnosis and of the surviving 30 percent, there will be a peri-operative mortality of 40 percent. Thus only 20 percent of patients survive this condition. It is important to state that the long-term survival reported for patients undergoing AAA surgery approximates that of age-matched populations. This is in contrast to patients undergoing a coronary bypass procedure, where the long-term survival is affected by factors such as hypertension, angina and peripheral vascular disease. If the condition is diagnosed electively, the mortality rate is reduced to less than 5 percent. The researcher obtained the records of 18 patients who had presented to the vascular service at the New Kingsbury Hospital with a diagnosis of a ruptured or acute symptomatic AAA. He interviewed the referring family doctor and also obtained information from the case records to determine whether there were missed opportunities for the detection of such aneurysms. The results of the research showed that 12 general practitioners (GP's) out of a group of 13, were unaware that abdominal ultrasound is a highly specific and sensitive method for detecting AAA's. Only one of the group of 13 GP's regularly screens for AAA. The diagnosis of AAA was missed in 12 of the 18 patients. In this series the mean diameter of the aorta was 7,67 cm which is considered to be easily palpable. Five of the patients were referred to specialists for incidental reasons and they all failed to detect the AAA. The majority of patients with AAA's have at least 2 associated risk factors. The patients consulted their GP at least 5 times over the 24 month period. The GP's are not aware of the different modes of presentation, associated risk factors nor the value of screening for AAA's. Ten of the group of 13 GP's profess to engage in some form of Continuing Medical Education (CME). I have suggested a few guidelines to encourage family physicians to screen for AAA in all males over the age of 60, especially if they have risk factors, such as hypertension, a current or former cigarette smoker, coronary artery disease, peripheral vascular disease and a family history of AAA. The examination should include a thorough abdominal palpation and referral for an abdominal ultrasound examination to obtain the precise diameter of the AAA as treatment depends on the size of the AAA.